Assessing social protection influence on health status in the European Union - Bocean, Claudiu George; Vărzaru, Anca Antoaneta (Frontiers in Public Health, 2024)
Introduction Health status and access to healthcare services are crucial factors that directly impact the well-being of individuals and societies. In the European Union (EU), social protection measures are significant in supporting citizens’ health and providing access to healthcare resources. Methods This study investigates the relationship between social protection and health status in EU countries. We collected data from Eurostat on the EU member states’ health status, healthcare expenditure, and social protection expenditure. The paper used structural equation modeling (SEM) and cluster analysis to analyze the complex interplay among these variables. Results Findings revealed a strong positive correlation between EU countries’ social protection expenditure and healthcare status. Higher social protection spending was associated with improved access to healthcare services and facilities. Moreover, the analysis showed that countries with higher social protection expenditure tended to exhibit better overall health status indicators among their populations. Discussion The results suggest that adequate social protection expenditure positively influences health status in the European Union. By investing in robust social protection programs, governments can enhance citizens’ access to healthcare services and resources, ultimately leading to improved health outcomes. These findings underscore the importance of prioritizing social protection policies to address health disparities and promote public health in the EU.